Prevalence and Associated Factors of Sensitization to Food Allergens in Congolese Children with Atopic Dermatitis - Masudi, Pascaline Ngolo; Nono, Seudjip; Bitingo, Pierre Kitha; Mwindulwa, Louis Kyembwa; Byemero, Desire Ndayazi; Okitotsho, Stanis Wembonyama (European Scientific Journal, ESJ, 2026)
Background: Research on the role of diet in the pathogenesis of atopic dermatitis remains a relatively underexplored field, particularly on the African continent and more specifically in the Democratic Republic of Congo. The objective of this study was to determine the prevalence and associated factors of sensitization to food allergens among Congolese children with atopic dermatitis. Methods: A cross-sectional descriptive and analytical study was conducted between June and September 2025. The study included 101 patients aged between six months and fourteen years, all diagnosed with atopic dermatitis and subjected to skin prick tests to detect food-related allergic reactions. Data collected were recorded and analyzed using the Statistical Package for Social Sciences version 27. Results: The study participation rate was 29.5%. Sensitization to at least one food allergen was observed in 35.6% of the subjects. The most common sensitizations were to peanuts (20.8%) and African eggplant (16.8%). Data analysis showed that food sensitization was significantly associated with several clinical and demographic variables, including age under one year (p = 0.002), male sex (p = 0.000), residence in an urban area (p = 0.004), late introduction of solid foods (weaning at ≥ 6 months) (p = 0.008), severe atopic dermatitis (p = 0.004), and early onset of dermatitis (≤ 3 months) (p = 0.001). Conclusion: A high prevalence of sensitization to food allergens, particularly peanuts and African eggplant, was found among Congolese children with atopic dermatitis. A significant association was also observed between this sensitization and several sociodemographic and clinical variables